Assessment of Coagulation by Thromboelastography During Ongoing Postpartum Hemorrhage: A Retrospective Cohort Analysis. (February 2020) - Rigouzzo, Agnes; Louvet, Nicolas; Favier, Rémi; Ore, Marie-Virginie; Piana, Federica; Girault, Laure; Farrugia, Magali; Sabourdin, Nada; Constant, Isabelle
Abstract : BACKGROUND: Rapid assessment of hemostasis during postpartum hemorrhage (PPH) is essential to allow characterization of coagulopathy, to estimate bleeding severity, and to improve outcome. Point of care (POC) coagulation monitors could be of great interest for early diagnosis and treatment of coagulation disorders in PPH. METHODS: Women with ongoing PPH >500 mL who clinically required an assessment of coagulation with thromboelastography (TEG) were included. The primary aim of this retrospective observational cohort study was to assess the predictive accuracy of TEG parameters for the diagnosis of coagulation disorders (hypofibrinogenemia ⩽2 g/L, thrombocytopenia ⩽80, 000/mm 3, prothrombin ratio ⩽50%, or activated partial thromboplastin time ratio ≥1.5) during PPH. The analyzed TEG parameters were Kaolin-maximum amplitude (K-MA), Kaolin-maximum rate of thrombus generation using G (K-MRTGG), functional fibrinogen-maximum amplitude (FF-MA), and functional fibrinogen-maximum rate of thrombus generation using G (FF-MRTGG). Secondary aims of this study were (1) comparison of the time delay between classical parameters and velocity curve–derived parameters (K-MA versus K-MRTGG and FF-MA versus FF-MRTGG) and (2) evaluation of the accuracy of TEG parameters to predict severe hemorrhage estimated by calculated blood losses. RESULTS: Ninety-eight patients were included with 98 simultaneous TEG analyses and laboratory assays. All parameters had an excellent predictive performance. For the Kaolin assay, no significant difference was evidenced between K-MA and K-MRTGG for the predictive performance for hypofibrinogenemia ⩽2 g/L and/or thrombocytopenia ⩽80, 000/mm 3 (respective area under the curve [AUC], 0.970 vs 0.981 ). For the functional fibrinogen assay, no significant difference was evidenced between FF-MA and FF-MRTGG for the predictive performance for hypofibrinogenemia ⩽2 g/L (respective AUC, 0.988 vs 0.974 ). For both assays, the time to obtain results was shorter for the velocity parameters (K-MRTGG: 7.7 minutes [2.4 minutes] versus K-MA: 24.7 minutes [4.2 minutes], P < .001; FF-MRTGG: 2.7 minutes [2.7 minutes] versus FF-MA: 14.0 minutes [4.3 minutes], P < .001). All TEG parameters derived from the Kaolin and functional fibrinogen assays and Clauss fibrinogen were significantly predictive of severe PPH >2500 mL. CONCLUSIONS: During PPH, when coagulation assessment is indicated, TEG provides a rapid and reliable detection of hypofibrinogenemia ⩽2 g/L and/or thrombocytopenia ⩽80, 000/mm 3 . No difference in performance was evidenced between the velocity-derived parameters (K-MRTGG and FF-MRTGG) and the classical parameters (K-MA and FF-MA). However, velocity-derived parameters offer the advantage of a shorter time to obtain results: FF-MRTGG parameter is available within ⩽5 minutes. POC assessment of hemostasis during PPH management may help physicians to diagnose clotting disorders and to provide appropriate hemostatic support.